Fluorine ion coupled high-entropy perovskite electrode material and preparation method thereof
Through fluorine ion coupling of high-entropy perovskite electrode materials, the problems of phase separation, insufficient catalytic activity and poor stability of SOEC cathode materials under high temperature conditions are solved, and efficient CO2 electrolysis and long-term stability are achieved.
Patent Information
- Application Number
- CN202510117307.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
AI Technical Summary
Existing SOEC cathode materials are prone to phase separation, insufficient catalytic activity and poor stability under high temperature reduction conditions.
Fluorine ion coupled high-entropy perovskite electrode material is prepared by electrospinning, sol-gel method or combustion method, and fluorine ions are introduced to weaken metal-oxygen bonds and promote the formation of oxygen vacancies through high-entropy structures.
It improves the adsorption and activation capabilities of CO2, enhances the long-term stability of CO2 electrolysis, and significantly improves the electrochemical performance of SOEC.
Smart Images

Figure CN119560572A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and particularly relates to a method for preparing a fluoride-ion-coupled high-entropy perovskite electrode material. Background Art
[0002] Solid oxide electrolysis cells (SOECs) are considered a promising and efficient energy conversion technology. However, due to cathode materials with insufficient electrocatalytic activity and stability, their large-scale commercial applications are severely limited. Currently, nickel-based ceramics, especially Ni-YSZ (yttria-stabilized zirconia), are considered the main cathode materials commonly used in SOECs due to their high electrolytic catalytic activity and good electrical conductivity. However, under high-temperature electrolysis conditions in pure carbon dioxide, the metal Ni catalyst is prone to coarsening, oxidation, and carbon deposition, resulting in rapid degradation of the performance of carbon dioxide electrolysis. Therefore, perovskite oxides with mixed ionic-electronic conductivity have been proposed to replace nickel-based ceramics as alternative cathode materials for carbon dioxide electrolysis in SOECs due to their superior redox stability.
[0003] Chinese Patent with Publication No. CN 119100464 A discloses a La-based fluorine-element-doped high-entropy perovskite oxide material, its preparation method and application. First, metal salts are calcined to prepare oxides, and then ammonium fluoride is used to incorporate fluorine elements. Although this method also forms a fluorine-containing high-entropy material, the preparation method is complex, the selection and configuration of metal elements are unreasonable, and the product particle size is large. Moreover, the secondary incorporation method makes the combination between elements not tight, which is not conducive to the generation of oxygen vacancies and the stability of the structure, resulting in that this material can only be applied to oxygen evolution electrocatalysis and cannot be applied to high-temperature fuel cells. Summary of the Invention
[0004] The present invention mainly provides a fluoride-ion-coupled high-entropy perovskite electrode material with high electrochemical performance, excellent thermal stability, and anti-carbon deposition ability, and it is applicable to solid oxide electrolysis cells to solve the problems that existing fuel electrode materials are prone to phase separation, insufficient catalytic activity, and poor stability under high-temperature reduction conditions: A fluoride-ion-coupled high-entropy perovskite electrode material, with the molecular formula La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0. 1O 3-X-δ F X , where 0.05 < x ≤ 0.2, δ is the oxygen vacancy content, 0 < δ ≤ 2; the configurational entropy S config ≥1.5R.
[0005] Furthermore, the molecular formula is La0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 2.9-δ F 0.1 .
[0006] Furthermore, the electrode material is prepared by electrostatic spinning, sol-gel method or combustion method.
[0007] A method for preparing the above-mentioned fluoride ion coupled high entropy perovskite electrode material is characterized by comprising the following steps: (1) dissolving a metal fluoride and a nitrate or oxide corresponding to the metal element in the molecular formula in a nitric acid solution in a stoichiometric ratio to obtain a solution containing metal cations; then, adding citric acid and ethylenediaminetetraacetic acid to the solution containing metal cations to obtain a mixed solution, adjusting the pH of the mixed solution by dropwise adding ammonia water, and stirring the mixed solution to obtain a sol; (2) drying the obtained sol on a hot plate and burning it to generate a precursor powder; (3) Calcine the precursor powder in an air atmosphere to obtain a perovskite electrode material.
[0008] Furthermore, in step (1), the molar ratio of the citric acid to the metal cation is 1.2-1.8:1; and the molar ratio of the citric acid to ethylenediaminetetraacetic acid is 1.2-1.8:1.
[0009] Furthermore, the pH value of the mixed solution in step (1) is adjusted to 7-8; the sufficient stirring in step (1) is stirring at room temperature until a dark brown sol is formed.
[0010] Furthermore, the temperature of the hot plate in step (2) is 200-300° C.; and the calcination in step (3) is performed at 1000-1100° C. for 3-5 hours.
[0011] An application of the above-mentioned fluoride ion coupled high entropy perovskite electrode material in the preparation of batteries.
[0012] Furthermore, the fluoride ion-coupled high-entropy perovskite electrode material is coated on one side of the barrier layer, dried and calcined to form a half-cell containing a fuel electrode, and then an air electrode is brushed on the other side to form a complete single cell.
[0013] Furthermore, the barrier layer is Gd 0.1 Ce 0.9 O 2-δ ; The air electrode adopts La 0.6 Sr 0.4 Co 0.2 Fe0.8 O 3-δ ; The coating thickness of the fuel electrode is 10~15μm; The coating thickness of the barrier layer is 5~10μm.
[0014] By adopting the above scheme, the method of the present invention has the following advantages: 1. This invention is the first to couple fluoride ions to high-entropy perovskite fuel electrode material La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 2.9-δ F 0.1 As a fuel electrode for solid oxide electrolyzers, the introduction of fluoride ions promotes the formation of oxygen vacancies by weakening the metal-oxygen bond and combining with the high entropy structure, thereby enhancing the adsorption and activation of CO2. In addition, the high entropy structure and fluorine doping effectively inhibit the Sr segregation phenomenon on the electrode surface, thereby enhancing the long-term stability of CO2 electrolysis. The synergistic strategy of combining high entropy engineering with anion doping provides great potential for the development of efficient and stable SOEC CO2 electrolysis electrodes.
[0015] 2. The electrode material sample of the present invention is composed of small particles connected to each other, forming a porous network structure. This porous structure has a potential enhancement effect on the gas diffusion performance and interface reaction kinetics of SOEC electrode materials.
[0016] 3. The introduction of La and Sr in the electrode material of the present invention can synergistically improve the electrochemical performance and chemical stability, optimize the crystal structure, oxygen ion transport and catalytic activity, and improve the thermal expansion coefficient matching to extend the battery life. The introduction of transition elements such as Fe, Co, Ni, and Mn enhances the electrocatalytic activity, electronic conductivity, and high-temperature stability, and regulates the crystal structure and oxygen vacancy concentration. The introduction of high-valent Mo ions improves the electrochemical performance and high-temperature stability of the material and enhances the stability of the crystal structure by generating oxygen vacancies, optimizing lattice symmetry, and regulating thermal expansion coefficients.
[0017] 4. The present invention directly introduces SrF precursor to prepare perovskite materials through a one-pot method. Compared with the subsequent high-temperature introduction of ammonium fluoride, it has uniform doping at a lower temperature, avoiding the problem of fluorine volatilization or uneven distribution during high-temperature treatment, ensuring the phase purity and lattice integrity of the material, thereby improving the structural stability and electrochemical performance. The material prepared by this method has good porosity and nanometer-scale particle size, which greatly increases the CO2 catalytic activity, showing 1.78A / cm at 800℃ and 1.5V voltage. 2 The ultra-high current density is 0.46Ω·cm 2 Low polarization impedance.
[0018] 5. After 100 hours of continuous operation at a high temperature of 750°C, the electrolysis current density of the single cell prepared by the electrode material of the present invention showed relatively stable characteristics, with a small decay amplitude, and the current density can be maintained above 80%. This result shows that the fluorine-doped high-entropy perovskite cathode of the present invention has good long-term stability in the CO2 electrolysis process.
[0019] 6. The single cell prepared by the electrode material of the present invention exhibits extremely low polarization impedance, indicating that the electrode material prepared by the present invention has strong catalytic activity; and exhibits extremely high current density, which indicates that F doping significantly enhances the electrochemical performance of SOEC. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 1 and 2 are X-ray diffraction patterns of the electrode materials of (a) Example 1 and (b) Comparative Example.
[0021] Figure 2 HR-TEM images of (a) the electrode materials of Example 1 and (b) the comparative example.
[0022] Figure 3 are transmission electron microscope (TEM) images of (a) the electrode materials of Example 1 and (b) the comparative example.
[0023] Figure 4 The EIS spectra are obtained by testing the electrode materials of Example 1 and the comparative example at an open circuit voltage of 800°C in a pure CO2 atmosphere.
[0024] Figure 5 It is the IV test curve obtained by testing the electrode materials of Example 1 and the comparative example in a pure CO2 atmosphere at 800°C.
[0025] Figure 6 This is a long-term stability test graph obtained by testing the electrode material of Example 1 at 750°C and 1.2V. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1: (1) According to the chemical formula La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni0.2 Mn 0.2 Mo 0.1 O 2.9-δ F 0.1 The stoichiometric ratio and the molar ratio corresponding to the number of elements are weighed and 1.955 g La2O3 is dissolved in 20 mL of dilute nitric acid solution as La 3+ Precursor, then, add 200 mL of water to the dilute nitric acid solution; add 1.48 g Sr(NO3)2, 2.424 g Fe(NO3)3·9H2O, 1.164 g Co(NO3)2·6H2O, 1.163 g Ni(NO3)2·6H2O, 1.004 g Mn(NO3)2·4H2O and 0.353 g (NH4)6Mo7O 24 ·4H2O metal precursors are added to the solution in sequence; at the same time, 0.125g of SrF2 as a strontium source and a fluorine source is added, and the mixture is mixed until the metal cations are completely dissolved to obtain a solution containing metal cations; (2) adding 12.6 g of citric acid (CA) and 11.69 g of ethylenediaminetetraacetic acid (EDTA) as a chelating agent and a combustion agent to the solution containing metal cations, and setting the molar ratio of CA, EDTA and total metal cations to 1.5:1:1; adjusting the pH value of the mixed solution to 7.0-8.0 by dropping ammonia water, and stirring at room temperature for 12 hours to form a dark brown sol; (3) The obtained sol was dried on a hot plate at 300°C and burned to generate a precursor powder. Finally, the precursor powder was calcined at 1000°C for 5 hours in an air atmosphere to prepare the target perovskite electrode material (i.e., LSFCNMM-F).
[0028] The X-ray diffraction pattern of the electrode material obtained in Example 1 is as follows: Figure 1 As shown in (a), no impurity phase was detected in the obtained sample, and it has a standard perovskite diffraction peak pattern, which is consistent with the typical orthorhombic perovskite structure (Pnma space group). This shows that a high-purity high-entropy perovskite material was successfully synthesized. Figure 2 (a) is the HR-TEM image of the electrode material of Example 1. It can be seen from the figure that the lattice spacing of its orthorhombic perovskite structure on the (112) crystal plane is 0.256 nm, which corresponds to the XRD result. It is confirmed that the high entropy perovskite material has been successfully synthesized.
[0029] Figure 3 The transmission electron microscope image in (a) shows that the prepared sample has a small and uniform particle size. The F doping does not affect the microscopic morphology of the high entropy perovskite. The sample is composed of small particles connected to each other, forming a porous network structure. This porous structure has a potential enhancement effect on the gas diffusion performance and interface reaction kinetics of SOEC electrode materials.
[0030] Example 2: The difference from Example 1 is that the chemical formula in step (1) is La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 2.95-δ F 0.05 ; The added amount of Sr(NO3)2 is 1.587g; The added amount of SrF2 is 0.0625g.
[0031] Example 3: The difference from Example 1 is that the chemical formula in step (1) is La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 2.8-δ F 0.2 ; The added amount of Sr(NO3)2 is 1.27g; The added amount of SrF2 is 0.25g.
[0032] Comparative Example: The difference from Example 1 is that the chemical formula in step (1) is La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 3-δ ; The added amount of Sr(NO3)2 is 1.693g. The target perovskite electrode material (ie, LSFCNMM) is prepared.
[0033] The X-ray diffraction pattern of the electrode material obtained in the comparative example is as follows: Figure 1 As shown in (b), it can be seen from the figure that the obtained sample is a high-purity high-entropy perovskite material. Figure 2 (b) is the HR-TEM image of the electrode material of the comparative example. It can be seen from the figure that the perovskite material was also successfully synthesized in the comparative example.
[0034] Figure 3 It can be seen from the transmission electron microscope image in (b) that the size of the prepared particles is uniform and similar to the morphology of Example 1, but the particle size is slightly larger than that of Example 1, indicating that fluorine doping does not change the morphology of the sample, but is conducive to reducing the particle size.
[0035] Test of Example Samples and Comparative Example Samples: To study the electrochemical performance of carbon dioxide electrolysis, the following structure electrolyte-supported cells were prepared: LSFCNM-F / GDC / LSGM / LSCF, LSFCNM / GDC / LSGM / LSCF. The specific preparation steps are as follows: First, polyvinyl alcohol (5% PVA) was used as a binder to mix La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ The (LSGM) powder was uniformly ground. Subsequently, the ground powder was dry pressed into a disc shape at 250MPa and sintered at a high temperature of 1450℃ for 5 hours to form a dense electrolyte structure, ensuring good conductivity and mechanical stability. Next, to prepare the electrode and barrier layer, the target powder was fully mixed with a binder (6% ethyl cellulose and 94% pine alcohol) in a mortar to make a uniform slurry. The barrier layer Gd 0.1 Ce 0.9 O 2-δ The (GDC) slurry was evenly applied on one side of the LSGM electrolyte disc and sintered at 1200°C for 5 hours (heating rate of 3°C / min) to form a dense and uniform barrier layer to improve the interface performance between the electrolyte and the fuel electrode. Subsequently, the electrode slurry (LSFCNMM-F / LSFCNMM) prepared in Example 1 and the comparative example was evenly applied on the surface of the GDC barrier layer, and the air electrode La was applied on the other side of the disc. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) slurry. Finally, the coated sample was calcined at 1000°C for 3 hours in an air atmosphere to form a single cell with a sandwich structure, in which the bonding interface between the electrolyte, barrier layer and electrode was optimized. The single cell prepared by this method showed excellent structural integrity and interface uniformity, providing basic support for subsequent research on its electrochemical performance of carbon dioxide electrolysis.
[0036] To study the electrochemical performance of the single cell, the anode of the single cell is facing upward and sealed in an alumina tube by ceramic sealant to ensure good airtightness. The experimental device is placed in a heating furnace and the test temperature is adjusted to 800°C. During the high-temperature carbon dioxide electrolysis process, pure carbon dioxide gas (flow rate 20mL / min) is introduced into the cathode side, while the anode side is directly exposed to the ambient air. The electrochemical test was carried out using a Zahner electrochemical workstation to evaluate the performance of single cells equipped with LSFCNMM-F and LSFCNMM electrodes of Example 1 and Comparative Example. At 10 5 Hz to 10 -1Electrochemical impedance spectroscopy (EIS) was recorded in the frequency range of 100 Hz. The current-voltage (IV) curve was obtained by scanning from open circuit voltage (OCV) to 1.6 V with a scan rate of 10 mV / s. The long-term stability of the single cell was tested under constant voltage conditions to further verify the electrolytic performance and system stability.
[0037] Figure 4 The EIS spectrum obtained by testing the LSFCNMM-F and LSFCNMM fuel electrodes of Example 1 and the comparative example at an open circuit voltage of 800°C pure CO2 atmosphere is shown. The impedance spectrum consists of a semicircle, which is divided into ohmic impedance (R Ω ) and polarization impedance (R p ), the ohmic impedance is the first x-intercept of the semicircular spectrum in the high-frequency region, which is usually related to ionic conduction through the electrolyte, electronic conduction within the battery components, and contact resistance. The polarization impedance is calculated by subtracting the ohmic impedance from the total resistance estimated using the second x-intercept of the spectrum in the low-frequency region, which is attributed to charge transfer reactions and mass transfer steps at the interface between the electrode and the electrolyte. Figure 4 It can be seen that the polarization impedance of the single cell equipped with the LSFCNMM-F fuel electrode of Example 1 is 0.46Ω·cm 2 , much lower than the comparative example of 0.91Ω·cm 2 , indicating that the electrode material prepared by the present invention has strong catalytic activity.
[0038] Figure 5 This is the IV curve obtained by testing the LSFCNMM-F fuel electrode of Example 1 and the LSFCNMM fuel electrode of the comparative example in a pure CO2 atmosphere at 800°C. The IV curve can be divided into three characteristic regions. The first region is the applied voltage range from open circuit voltage (OCV) to 0.25V, at which point the current density increases with increasing voltage, mainly due to the enhancement of the oxygen pumping process and the change in the valence state of the B-site transition metal. This process reflects the significant contribution of oxygen ion migration and surface redox activity of the electrode material at lower voltages. The second region is located between 0.2 and 0.8V, at which point the current density tends to be stable and does not increase significantly with increasing voltage. In this region, the applied voltage is insufficient to drive effective carbon dioxide electrolysis and can only maintain the battery to a state of reaction equilibrium, indicating that the reaction kinetics at the electrode and electrolyte interface are limited at this stage. The voltage in the third region exceeds 0.8V, at which point the current density rises rapidly, marking a significant occurrence of carbon dioxide electrolysis reaction. Generally speaking, higher current densities indicate that SOEC has superior carbon dioxide electrolysis performance. By Figure 5It can be seen that the single cell equipped with the LSFCNMM-F fuel electrode of Example 1 exhibits an extremely high current density, which indicates that F doping significantly enhances the electrochemical performance of SOEC. At 800°C and 1.5V, the single cell using the LSFCNMM-F cathode of Example 1 has a current density of up to 1.78A / cm 2 , compared to 1.43A / cm 2 , with significant improvement.
[0039] Figure 6 The long-term durability performance test of CO2 electrolysis was carried out for a single cell using the LSFCNMM-F electrode material of Example 1 at 1.2V and 750°C. After 100 hours of continuous operation, the electrolysis current density of the single cell showed relatively stable characteristics with a small decay. It is worth noting that compared with the initial current density, the decay rate of the single cell using the electrode material of the present invention was 18.2%. This result shows that the fluorine-doped high-entropy perovskite electrode has good long-term stability in the CO2 electrolysis process.
[0040] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A fluoride ion coupled high entropy perovskite electrode material, characterized in that: The molecular formula is La 0.6 Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 3-X-δ F X , where 0.05≤x≤0.2, δ is the oxygen vacancy content, 0<δ≤2; configuration entropy S config ≥1.5R.
2. The fluoride ion coupled high entropy perovskite electrode material according to claim 1, characterized in that: The molecular formula is La 0. 6Sr 0.4 Fe 0.3 Co 0.2 Ni 0.2 Mn 0.2 Mo 0.1 O 2.9-δ F 0.1 .
3. The fluoride ion coupled high entropy perovskite electrode material according to claim 1, characterized in that: The electrode material is prepared by electrostatic spinning, sol-gel method or combustion method.
4. A method for preparing the fluoride ion coupled high entropy perovskite electrode material according to claim 1, characterized in that: The following steps are involved: (1) dissolving a metal fluoride and a nitrate or oxide corresponding to the metal element in the molecular formula in a nitric acid solution in a stoichiometric ratio to obtain a solution containing metal cations; then, adding citric acid and ethylenediaminetetraacetic acid to the solution containing metal cations to obtain a mixed solution, adjusting the pH of the mixed solution by dropwise adding ammonia water, and stirring the mixed solution to obtain a sol; (2) drying the obtained sol on a hot plate and burning it to generate a precursor powder; (3) Calcine the precursor powder in an air atmosphere to obtain a perovskite electrode material.
5. The method for preparing the fluoride ion coupled high entropy perovskite electrode material according to claim 4, characterized in that: In step (1), the molar ratio of the citric acid to the metal cation is 1.2-1.8:1; and the molar ratio of the citric acid to ethylenediaminetetraacetic acid is 1.2-1.8:
1.
6. The method for preparing the fluoride ion coupled high entropy perovskite electrode material according to claim 4, characterized in that: The pH value of the mixed solution in step (1) is adjusted to 7-8; the sufficient stirring in step (1) is stirring at room temperature until a dark brown sol is formed.
7. The method for preparing the fluoride ion coupled high entropy perovskite electrode material according to claim 4, characterized in that: The temperature of the hot plate in step (2) is 200-300° C.; and the calcination in step (3) is performed at 1000-1100° C. for 3-5 hours.
8. Use of the fluoride ion coupled high entropy perovskite electrode material according to any one of claims 1 to 3 in the preparation of a battery.
9. Use of the fluoride ion coupled high entropy perovskite electrode material in preparing a battery according to claim 8, characterized in that: The fluoride ion-coupled high-entropy perovskite electrode material is applied to one side of the barrier layer, dried and calcined to form a half-cell containing a fuel electrode, and then an air electrode is applied to the other side to form a complete single cell.
10. The use of the fluoride ion coupled high entropy perovskite electrode material in preparing a battery according to claim 9, characterized in that: The barrier layer is Gd 0.1 Ce 0.9 O 2-δ ; The air electrode adopts La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ ; The coating thickness of the fuel electrode is 10~15μm; The coating thickness of the barrier layer is 5~10μm.
Citation Information
Patent Citations
Perovskite oxide catalyst and preparation method and application thereof
CN109759077A
Electric energy / value-added chemical symbiotic fuel cell and preparation method thereof
CN112687900A
R-P type layered medium-entropy perovskite structure cathode material and preparation method thereof
CN114824303A
Full-high-entropy proton ceramic fuel cell and preparation method thereof
CN115763835A
High-entropy perovskite cathode material and preparation method and application thereof
CN115832339A